Beneficial effect of monoclonal antibody to interleukin 2 receptor on activated T cells in rheumatoid arthritis. Issue 5 (May 1989) - Kyle, V; Coughlan, R J; Tighe, H; Waldmann, H; Hazleman, B L
Abstract : Campath 6, a rat IgG2b monoclonal antibody to the interleukin 2 receptor on activated T cells, was used to treat three patients with active rheumatoid arthritis unresponsive to conventional treatment. Two patients had an excellent response for about three months. There were no significant side effects. The results suggest that activated T cells are of importance in the pathogenesis of rheumatoid arthritis. Although infusions of rat monoclonal antibodies could not be repeated because of the risk of sensitisation, the development of humanised monoclonal antibodies targeted against specific T cell sets would allow repeated courses of treatment to be given.